2011
DOI: 10.1158/1055-9965.epi-11-0300
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D-Related Genetic Variants, Interactions with Vitamin D Exposure, and Breast Cancer Risk among Caucasian Women in Ontario

Abstract: Background: Vitamin D, from diet and sunlight exposure, may be associated with reduced breast-cancer risk. This study investigated if candidate gene variants in vitamin D pathways are associated with breast cancer risk, or modify the associations between breast cancer and vitamin D exposure.Methods: Breast cancer cases aged 25 to 74 years were identified from the Ontario Cancer Registry (histopathologically confirmed and diagnosed [2002][2003] and population-based controls were identified through random digit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
77
6

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(93 citation statements)
references
References 50 publications
10
77
6
Order By: Relevance
“…A significant association between the T allele in rs7041 and breast cancer has been reported in Caucasian women in Canada (Anderson et al, 2011). To our knowledge, our current study reports a significant association between rs7041 and lung cancer for the first time.…”
Section: Discussionsupporting
confidence: 59%
“…A significant association between the T allele in rs7041 and breast cancer has been reported in Caucasian women in Canada (Anderson et al, 2011). To our knowledge, our current study reports a significant association between rs7041 and lung cancer for the first time.…”
Section: Discussionsupporting
confidence: 59%
“…This protein has been noted as having a protective effect in breast cancer by facilitating transport of vitamin D metabolites (13) and has been shown to be downregulated in the serum of breast cancer patients (26). Some studies suggest that specific genetic variants of VDBP influence a woman's risk of developing breast cancer (27). In the aggregate, our results show an increase in plasma levels of VDBP in rats fed a high n-3:n-6 fatty acid ratio which provides support for an additional possible mechanism of chemoprevention by n-3 fatty acids.…”
Section: Discussionmentioning
confidence: 99%
“…Case-control studies on Fok1 in breast cancer showed some evidence of increased risk among ff carriers (Sinotte et al, 2008;Gapska et al, 2009;McKay et al, 2009), which was confirmed by some later metaanalysis Tang et al, 2009;. However, these studies also reported some decreased risk among ff carriers (Anderson et al, 2011), or no association with breast cancer (Curran et al, 1999;Guy et al, 2004;John et al, 2007;Abbas et al, 2008;Engel et al, 2012;Rollison et al, 2012;Fuhrman et al, 2013;Mishra et al, 2013;Shahbazi et al, 2013). Similarly, mixed results have been observed concerning the relationship between other polymorphisms and the risk of breast cancer development.…”
Section: Introductionmentioning
confidence: 89%
“…2013; Shahbazi et al, 2013) but not in others (Buyru et al, 2003;Hefler et al, 2004;VandeVord et al, 2006;Trabert et al, 2007;Sinotte et al, 2008;Gapska et al, 2009;McKay et al, 2009;Anderson et al, 2011;Rollison et al, 2012;Mishra et al, 2013); Apa1 was found with positive relationship in some breast cancer studies (Curran et al, 1999;Sillanpaa et al, 2004;Dalessandri et al, 2012), but negative in others (Cui et al, 2001;Hou et al, 2002;Chakraborty et al, 2009;Anderson et al, 2011;Engel et al, 2012;Mishra et al, 2013); the same as Taq1, with associations in some studies (Cui et al, 2001;, but not in others (Curran et al, 1999;Dunning et al, 1999;Lundin et al, 1999;Hou et al, 2002;Newcomb et al, 2002;Buyru et al, 2003;Sillanpaa et al, 2004;John et al, 2007;Abbas et al, 2008;Chakraborty et al, 2009;Gapska et al, 2009;Anderson et al, 2011;Engel et al, 2012;Mishra et al, 2013); Cdx2, positive in some studies (Anderson et al, 2011;Yao et al, 2012; but not in others (Abbas et al, 2008;Zhou et ...…”
mentioning
confidence: 93%